ANALISIS PENGARUH EFISIENSI MODAL KERJA, LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS Studi Kasus pada PT. Telekomunikasi Indonesia, Tbk - Setyo Budi Nugroho (Jurnal Ilmu Administrasi Bisnis, 2012)
Every company aims to find profitability. To achieve expected earnings, management should able to take proper discretion in investing financial resources available so will obtain liquidity and solvency in sufficient condition and adequate working capital efficiency and finally the expected profitability will obtained. The purpose of this research is to find out influence of working capital efficiency, liquidity, solvency to profitability at PT Telekomunikasi Indonesia. It took time series data from financial statements in period 2006 to 2010. Data collection technique is through documentation. Data source obtained from Indonesia Stock Exchange website (Internet Data Exchange/IDX). Data get analyzed by using classical assumption test, simple and multiple linear regression, and hypothesis testing using T test and F test. Based on result of this research is known that there is no significantly influence between working capital efficiency, Liquidity and Solvency to profitability.